Neonatal outcome of babies born with congenital anomalies after pediatric surgery - Sharma, Snigdha; Sharma, Arti; Maletha, Madhukar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Congenital anomalies are the major cause of adverse neonatal outcome and mortality. Some congenital anomalies are correctable and there is immense role of pediatric surgery in treatment of these anomalies. The aim of this study was to determine the pattern of congenital anomalies and to evaluate clinical outcome of babies after surgical intervention. Methods: This hospital-based cross-sectional study was carried out in the Obstetrics and Gynecology department during the period of 1 year. All the delivered babies in this hospital during this period were examined by obstetricians and pediatricians for the presence of various congenital anomalies. Babies with correctable anomalies were operated by the Pediatric Surgery Department and outcome of babies at the time of discharge was included. Data were entered into a case record form and then in the excel sheet and were analyzed statistically. Results: During the study period, 1670 babies were delivered in our institution; of which, 32 babies had congenital malformations, giving the prevalence of 1.91%. The system involved predominantly was the gastrointestinal (GI) system (80%). Pregnancy with congenital malformation were associated with malpresentation, anemia and polyhydramnios. Overall, most babies operated for pediatric surgery had good outcome. Conclusions: Pre pregnancy high-dose folic acid supplementation, regular antenatal visits, and prenatal diagnosis are recommended for prevention, early detection and management of congenital anomalies. There is great importance of Level II and NT NB Scan. Pediatric surgery is a boon in babies with correctable anomalies.